STUDENTS’ RESPONSES TOWARD TEACHERS’ QUESTIONS IN SENIOR HIGH SCHOOL 8 BENGKULU - Evis Sumilia; Hilda Puspita; Elfrida Elfrida (Universitas Galuh, 2019)
Abstract: The aims of this research were to find out kinds of student response and the most dominant response used by the second grade students in Senior High School. The researcher was designed as a descriptive quantitative research. The population of the research was second grade student in Senior High School 8 Bengkulu. The samples were 60 students. The data were collected by using a set of questionnaire. There were 25 statements of students’ responses which consisted of five aspects by Moskowitzs in Brown (2001). They were student response (specific), student response (open-ended or student initiated), confusion, silence and nonverbal. The result of this study showed the students of Senior High School 8 Bengkulu preferred to use five aspects of the student response i.e., student response (specific), student response (open-ended or student initiated), confusion, silence and nonverbal. In addition, the most dominant response used by the student is student response (specific). The student more interested in using response specific in answering the teacher question. Keywords: Students’ Responses, Teachers’ Questions, Classroom Interaction